The prevalence and risk factors of atopic dermatitis in 6-8 year-old first graders in Taipei - Ciao-Lin Ho; Lu-I Chang; Wei-Fong Wu (Elsevier, 2019)
Background: Despite the advance in the understanding of etiology, pathophysiology and diagnosis of atopic dermatitis (AD), its prevalence has increased annually in Taiwan. Purposes: The purpose of this study is to explore the prevalence, and personal and environmental risk factors of AD. Methods: A cross-sectional survey was conducted via health centers of elementary schools in Taipei city. We used the Chinese version of ISAAC questionnaire to examine possible personal and environmental risk factors of AD. Questionnaires were completed by parents or guardians of first graders (6-8 year-old) who agreed to participate in this study. Logistic regression was conducted to examine possible personal and environmental factors related to AD (in early life and currently). Results: The 12-month prevalence of AD (in the past 12 months) was 10.7% (2683/24,999) among 6- to 8-year-old first graders in Taipei. Forty-five percent of first graders with AD had their first episode of AD symptoms before the age of two. Children with asthma history were 1.65 times (95% CI: 1.51-1.79, p < 0.001) and children with rhinitis were 2.57 times (95% CI: 2.34-2.84, p < 0.001) more likely to have AD than those without the conditions. Compare to their counterarts, children who used antibiotics during their first year of life (OR = 1.37, 95% CI: 1.22-1.53, p < 0.001) and who had bronchiolitis before the age of two (OR = 1.47, 95% CI: 1.33-1.63, p < 0.001) had a higher chance to have AD during the last 12 months of the study. However, receiving breastfeeding for less than 4 months (OR = 0.75, 95% CI: 0.67-0.83, p < 0.001) and having older siblings (OR = 0.83, 95% CI: 0.76-0.92, p < 0.001) had 25% and 17% reduced risks for AD in the 12 months before this study, respectively. Conclusion: Our study verified personal and environmental risk factors of AD in children in Taiwan. Based on the results, we propose that avoiding bronchiolitis before the age of two, using antibiotics properly in babies, and providing diet counseling for breastfeeding mothers may be good prevention strategies of AD. Key Words: Atopic dermatitis, Environmental risk factors, First graders